Asymmetric total synthesis of (2S,3S)-3-hydroxypipecolic acid - Chavan, Subhash P.; Dumare, Nilesh B.; Harale, Kishor R.; Kalkote, Uttam R. (Tetrahedron Letters, 2011)
A synthetic route to (2S,3S)-3-hydroxypipecolic acid was achieved from readily available nonchiral pool starting material cis-2-butene-1,4-diol and involved Claisen orthoester rearrangement, Sharpless asymmetric dihydroxylation and intramolecular lactamisation of azido lactone as the key steps. (C) 2010 Elsevier Ltd. All rights reserved.

Convenient formal synthesis of (2S,3S)-3-hydroxy pipecolic acid - Chavan, Subhash P.; Harale, Kishor R.; Dumare, Nilesh B.; Kalkote, Uttam R. (Tetrahedron-Asymmetry, 2011)
A convenient synthesis of (2S,3S)-3-hydroxy pipecolic acid starting from inexpensive and easily available L-(+)-tartaric acid has been described. (C) 2011 Elsevier Ltd. All rights reserved.

Chiron approach to formal synthesis of both antipodes of cis 3-hydroxypipecolic acid - Chavan, Subhash P.; Khairnar, Lalit B.; Chavan, Prakash N.; Dumare, Nilesh B.; Kalbhor, Dinesh B.; Gonnade, Rajesh G. (Tetrahedron Letters, 2014)
The efficient and practical formal syntheses of both enantiomers of cis 3-hydroxypipecolic acid were accomplished from cis aziridine-2-carboxylate as the common synthetic precursor. The key steps involved are stereo and regioselective aziridine ring opening, reductive cyclization and selective N-debenzylation over O-debenzylation reactions. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: 3-Hydroxypipecolic acid; Aziridine ring opening; Aziridine-2-carboxylate; Piperidine alkaloids; Selective debenzylation

Novel, concise and efficient protocol for non-natural piperidine compounds - Chavan, Subhash P.; Dumare, Nilesh B.; Pawar, Kailash P. (RSC Advances, 2014)
Formal synthesis of L-altro-1-deoxynojirimycin, cis-3-hydroxypipecolic acid along with synthesis of (R)-piperidinol and a conceptually different advanced intermediate for non-natural piperidine alkaloids is reported from cis-butene-1,4-diol. The key reactions involved are Johnson-Claisen rearrangement, Sharpless asymmetric dihydroxylation, reductive lactamization and novel regioselective elimination.

Total syntheses of D-allo-1-deoxynojirimycin and L-talo-1-deoxynojirimycin via reductive cyclization - Chavan, Subhash P.; Dumare, Nilesh B.; Pawar, Kailash P. (RSC Advances, 2014)
Synthesis of a polyhydroxypiperidine framework for L-talo-1-deoxynojirimycin and D-allo-1-deoxynojirimycin was achieved from L-tartaric acid by employing flash dihydroxylation and reductive lactamisation as the key steps.

Formal syntheses of (2R,3R)-3-hydroxy pipecolic acid and (2R,3S)-3-hydroxy pipecolic acid from L-ascorbic acid - Chavan, Subhash P.; Dumare, Nilesh B.; Pawar, Kailash P. (Tetrahedron Letters, 2015)
Formal syntheses of both cis and trans 3-hydroxy pipecolic acids is achieved from L-ascorbic acid. Present synthesis describes use of chiral pool approach in which epimerization, Staudinger reaction and Cyclization reactions were employed as key steps. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: 3-Hydroxy pipecolic acid; cyclization; Epimerization; L-Ascorbic acid

Asymmetric total synthesis of L-allo-1-deoxynojirimycin - Chavan, Subhash P.; Dumare, Nilesh B.; Pawar, Kailash P.; Chavan, Prakash N.; Khairnar, Lalit B. (Arkivoc, 2016)
Asymmetric total synthesis of L-allo-1-deoxynojirimycin (L-allo-DNJ) was achieved from cis-butene-1,4-diol by employing Sharpless asymmetric dihydroxylation, stereoselective flash dihydroxylation and ring enlargement reactions as key steps.
Keywords: diastereoselective flash dihydroxylation; ring-enlargement reaction; sharpless asymmetric dihydroxylation

Chiron approach to formal synthesis of both antipodes of cis 3-hydroxypipecolic acid (vol 55, pg 6423, 2014) - Chavan, Subhash P.; Khairnar, Lalit B.; Chavan, Prakash N.; Dumare, Nilesh B.; Kalbhor, Dinesh B.; Gonnade, Rajesh G. (Tetrahedron Letters, 2020)

Formal Synthesis of Corynanthe Indole Alkaloid (±)-Mitralactonine: Construction of α-Hydroxy-Keto Functionalized Tetracyclic Skeleton - Dumare, Nilesh B.; Sharma, Pallavi; Sivappa, Rasapalli; Chavan, Subhash P. (Chemistryselect, 2025)
An efficient synthesis of a tetracyclic skeleton common to many corynanthe alkaloids was accomplished in 10 linear steps starting from a known tetrahydro beta-carboline intermediate. The tetracyclic alpha-hydroxy keto functionalized advanced precursor of (+/-)-mitralactonine was realized using Wittig olefination, ketohydroxylation of a trisubstituted alkene, and a tandem amine unmasking-intramolecular nucleophilic displacement reaction for C-N bond formation of C/D-rings.
Keywords: alpha-hydroxy keto; beta-carboline; corynanthe alkaloid; intramolecular N-alkylation; mitragynine